Reciprocal Relationship between Taxpayer’s Compliance and Governance Quality - Masri, Indah; Chasbiandani, Tryas; Rasyid, Diandra Kamila; Nur’Aini, Nur’Aini (International Journal of Economics and Financial Issues, 2024)
This study aims to test the existence of a reciprocal relationship between taxpayer compliance and governance quality. From the first model with governance quality as a mediating variable, it is proven that it can mediate the level of taxpayer knowledge so that it will be able to strengthen the level of taxpayer compliance further through governance quality. However, governance quality cannot be a mediating variable for tax morale. From the second model, with taxpayer compliance as the mediating variable, it is proven that it can mediate the level of taxpayer morale so that the role of taxpayer compliance further strengthens the level of governance quality. However, for tax knowledge, the role of tax compliance cannot be a mediating variable.